# Reduce Each of the Following Expressions to the Sine and Cosine of a Single Expression: √ 3 Sin X − Cos X - Mathematics

Short Note

Reduce each of the following expressions to the sine and cosine of a single expression:

$\sqrt{3} \sin x - \cos x$

#### Solution

$\text{ Let } f\left( x \right) = \sqrt{3} \sin x - \cos x$
$\text{ Dividing and multiplying by }\sqrt{3 + 1}, i . e . \text{ by 2, we get }:$
$f\left( x \right) = 2\left( \frac{\sqrt{3}}{2} \sin x - \frac{1}{2} \cos x \right)$
$\Rightarrow f(x) = 2\left( \cos\frac{\pi}{6}\sin x - \sin\frac{\pi}{6}\cos x \right)$
$\Rightarrow f(x) = 2\sin\left( x - \frac{\pi}{6} \right)$
$\text{ Again },$
$f\left( x \right) = 2\left( \frac{\sqrt{3}}{2} \sin x - \frac{1}{2} \cos x \right)$
$\Rightarrow f\left( x \right) = 2\left( \sin\frac{\pi}{3} \sin x - \cos\frac{\pi}{3} \cos x \right)$
$\Rightarrow f\left( x \right) = - 2\cos\left( \frac{\pi}{3} + x \right)$

Is there an error in this question or solution?

#### APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 7 Values of Trigonometric function at sum or difference of angles
Exercise 7.2 | Q 2.1 | Page 26